Efficiency improvement of GaAs Quantum Dot in GaAs1-xPx matrix for solar cell applications. (May 2020) - Guesmi, H.; Aissat, A.; Safi, M.; Berbezier, I.
Abstract: In this paper, we present simulations and the optimization of electrical and optical properties of GaAs Quantum Dots (QD) in a GaAs1-x Px matrix. Our results showed that 25 GaAs/GaAs1-x Px QD layers provide a relative enhancement of 41.34% and 75.40% of the short-circuit current and efficiency, respectively. With the same number of the QD layers, the External Quantum Efficiency (EQE) measurement shows that the absorption range edge of low energy photons has been extended from 875 to 1200 ​nm (ΔEQE ​= ​25%). The temperature effect has been studied for a different number of QD inserted. The optimal conversion efficiency of 25 QD layers is degraded from 23.50% to 18.70% by increasing the temperature from 273 ​K to 350 ​K. Moreover, the electrical features obtained and EQE measurements for GaAs/GaAs1-x Px QDSC have been compared with those obtained for In0.47 Ga0.53 As/GaAs0.86 P0.14 QDSC, In0.167 Ga0.53 As/GaAs and GaAs reference cell, in order to show the better structure. Highlights: GaAs/GaAsP QDSC has been simulated and optimized. An efficiency of 22% is obtained with 25 GaAs/GaAsP QD layers. The comparison has shown that GaAs QDs in GaAsP matrix are better for near-IR absorption than InGaAs. The absorption edge of GaAs was extended from 870 ​nm to 1200 ​nm with QDs insertion. A high temperature provides a relative decrease in the efficiency of about 20.30%.